Living in fear : the experiences of parents of political activists in "coloured" Cape Flats townships, 1985-1988 : a social-psychological study - Syren, Christian J (1989)
Bibliography: pages 212-218.The present is a social-psychological study which describes and analyses the experiences of parents of political activists in "coloured" Cape Flats townships against the background of the socio-political upheaval in South Africa during the 1985/86 rebellion and thereafter. An ethnographic research method was used due to its suitability in terms of accessing the phenomena under study, and due to the theoretical problems associated with the use of traditional social psychological models in the South African context; it was argued that it is necessary to articulate the micro- and macro levels of social phenomena at the point of their intersection to do social psychology in an oppressive context. Outlines of the 1985/86 rebellion, which emphasized the role of youth and students, and of the methods of operation of the South African Police, from a historical perspective, were given as a backdrop against which the analyses of the empirical data were presented. The concrete experiences of the parents with respect to various forms of political repression were described and situated as specific stressors in their everyday lives; police presence, visits and searches of their homes, having a child 'on the run', detention without trial of their children, and the prevalent fear of being informed upon. While the particularly stressful aspects of these experiences were highlighted, they were moreover found to have had significant consequences in terms of contributing to the development of the parents' politicization and engagement in the political activities of their own children. These experiences were furthermore found to have precipitated the parents' own gradual involvement in support and other activities offered by progressive organizations, which reinforced the development of an outlook of resistance towards the state. Although the security forces' engineering of a climate of fear in the townships was portrayed as initially being a pervasive aspect of daily life and a powerful deterrent to parental involvement, it later, on the basis of commonality of experiences of victimization and persecution, forged communality of spirit and unity in resistance. The parents' experiences were first and foremost found to be characterized by fundamental emotional intra-personal conflict, and the need for further research of the psychological sequelae of political persecution and repression was stressed. The thesis was concluded by a comparison of some central findings which related to international as well as local research